Sperm morphology and testis histological changes in 12% high cholesterol diet administered rats following Tualang honey supplementation and diet modifications - Hasan, Sakiinah; Abdul Rahim, Roslina; Alias, Mohd Afzal; Muhammad, Siti Aeshah @ Naznin; Abdullah, Nor Zamzila; Abdul Razak, Redzuan Nul Hakim (2021)
Background: Hypercholesterolaemia is recognized as a factor associated with male infertility. However, currently, there is limited therapy available. Tualang honey (TH) is a type of Malaysian polyfloral wild honey produced by the rock bee (Apis dorsata) proven to exert both anti-inflammatory and anti-oxidative effects. Objective: This study aimed to determine the effects of TH coupled with diet modification on sperm morphology and testis histology of 12% high cholesterol diet (HCD) administered rats. Methodology: Twenty rats were divided into 4 groups. Control group were fed with standard diet for 20 weeks. The other 3 groups were fed with 12%HCD for 16 weeks. Then, group A rats were not treated and continued HCD. Group B rats were supplemented with TH (3.0g/kg) and continued HCD, while group C was given TH (3.0g/kg) but was changed to a normal diet for 4 weeks. At the end of 20 weeks, the left testis was collected for histology analysis and the cauda epididymis was collected to analyse the sperm parameter. Results: Compared to control, group A showed significant decrease in the percentage of normal sperm morphology (p<0.001). In contrast, group B and C demonstrated significant improvement in sperm morphology compared to group A (p<0.001). Group C showed better improvement in the percentage of normal sperm morphology compared to group B although not significant (p>0.05). However, there are no significant changes in Johnsen testicular histology scoring between the groups. Conclusion: Diet modification in addition to TH supplementation may further improve male fertility in HCD rats. Based on our findings, there is a need to further explore the potential TH in improving male infertility associated with hypercholesterolaemia.